2005
DOI: 10.1086/427963
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Pluto's Atmosphere from the 2002 August 21 Stellar Occultation

Abstract: We have observed the 2002 August 21 occultation by Pluto of the R ¼ 15:7 mag star P131.1, using 0.5 s cadence observations in integrated white light with the Williams College frame-transfer, rapid-readout CCD at the 2.24 m University of Hawaii telescope. We detected an occultation that lasted 5 minutes, 9:1 AE 0:7 s between half-light points. The ''kinks'' in the ingress and egress parts of the curve that were apparent in 1988 had become much less pronounced by the time of the two 2002 occultations that were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…The minimum value of χ 2 m then obtained with a global fit to all five light curves corresponds to T ∞ = 107 ± 3.5 K, the error bar stemming from the usual χ 2 m + 1 criterion. Our value for T ∞ is consistent with other results in 1988, 2002, and 2006, e.g., T ∞ = 104 ± 2 K (Pasachoff et al 2005), T ∞ = 102 ± 4 K on average (Elliot et al 2007), T ∞ ≈ 101 K (Sicardy et al 2003), and T ∞ = 104 ± 3 K (Young et al 2008). Elliot et al (2007) and Young et al (2008) also evoke the detection of a small negative temperature gradients of ∼−0.1-0.2 K km −1 in the (almost) isothermal upper part, possibly associated with CO cooling.…”
Section: Sensitivity To the Atmospheric Parameterssupporting
confidence: 93%
“…The minimum value of χ 2 m then obtained with a global fit to all five light curves corresponds to T ∞ = 107 ± 3.5 K, the error bar stemming from the usual χ 2 m + 1 criterion. Our value for T ∞ is consistent with other results in 1988, 2002, and 2006, e.g., T ∞ = 104 ± 2 K (Pasachoff et al 2005), T ∞ = 102 ± 4 K on average (Elliot et al 2007), T ∞ ≈ 101 K (Sicardy et al 2003), and T ∞ = 104 ± 3 K (Young et al 2008). Elliot et al (2007) and Young et al (2008) also evoke the detection of a small negative temperature gradients of ∼−0.1-0.2 K km −1 in the (almost) isothermal upper part, possibly associated with CO cooling.…”
Section: Sensitivity To the Atmospheric Parameterssupporting
confidence: 93%
“…Considering the similarities in composition and size of Pluto and 2005 FY 9 , and considering that Pluto has an atmosphere (e.g., Cruikshank & Silvaggio 1980;Fink et al 1980;Pasachoff et al 2005), the possibility arises that 2005 FY 9 also has an atmosphere. According to Elliot & Kern (2003), three conditions must be satisfied for a TNO-like object to have a bound atmosphere: (1) the body must have an inventory of volatiles on its surface that can sublimate; (2) the temperature must lie within the correct range -high enough for adequate vapour pressure, but not so high that the atmosphere would escape into space; (3) the body mass must be sufficient to retain an atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…This occultation revealed that Pluto's atmospheric pressure had approximately doubled (Elliot et al, 2003;Sicardy et al, 2003;Pasachoff et al, 2005). With Pluto crossing the galactic plane, occultations in 2006occultations in , 2007occultations in , 2008occultations in , 2009occultations in , and 2010occultations in were observed (summarized in Young, 2013.…”
Section: Stellar Occultationsmentioning
confidence: 94%